2019
DOI: 10.1590/1981-6723.20817
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological reference material (bacterial and fungal domains): Definition, production rules, use and need for establishment in Brazil

Abstract: Reference materials are crucial for laboratory quality assurance. They are widely used for the internal quality control of analytical tests, in the validation of methodologies and as test items in proficiency tests. Microbiological reference materials are represented mainly by reference strains, whose use in laboratory internal quality control is unquestionable and recommended by several microbiological manuals. In Brazil, the practice of producing microbiological reference materials has advanced in recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…From the analysis of the selected studies, we found that most of the evaluated strains used in the studies are reference strains, which is very important for the evaluation of the research results because reference strains are used in product testing, as positive and negative controls, as indicator organisms, or as identification standards, thus ensuring the quality of laboratory activities in microbiological analyses [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis of the selected studies, we found that most of the evaluated strains used in the studies are reference strains, which is very important for the evaluation of the research results because reference strains are used in product testing, as positive and negative controls, as indicator organisms, or as identification standards, thus ensuring the quality of laboratory activities in microbiological analyses [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reference materials (RM) are crucial for laboratory quality assurance. They are widely used for the internal quality control of analytical tests, in the validation of methodologies and as test items in proficiency tests 1 . Proficiency testing is a type of systems audit or external assessment, a check on the entire laboratory testing system.…”
Section: Introductionmentioning
confidence: 99%